Statistical Approach to the Analysis of the Corrosive Behaviour of NiTi Alloys under the Influence of Different Seawater Environments - Nataša Kovač; Špiro Ivošević; Gyöngyi Vastag; Goran Vukelić; Rebeka Rudolf (Applied Sciences, 2021)
Probabilistic models of corrosion rate estimation in the case of two NiTi alloys obtained by different technological processes are analysed in this paper. The depth of corrosion was measured by focused ion beam analysis on a metal surface that was not protected by an anti-corrosion coating. The samples were exposed to the influence of three different seawater environments, and empirical data were obtained in a systematic measurement procedure after 6, 12 and 18 months. Assuming that corrosion processes begin immediately after exposure of the samples to the influence of the seawater environment, and observing the corrosion rate as a random variable affected by various stochastic processes, the formed standard linear corrosion model was analysed by a statistical approach. The three best-fitted three-parameter distributions which can describe the changes in the corrosion rate for NiTi alloys exposed to the influence of the seawater environment adequately were obtained by fitting the continuous theoretical distributions. Adequate statistical tests showed similarities and differences in the behaviour of the two observed NiTi alloys from the point of view of corrosion processes caused by air, tide and sea.